A Case Study in Architecture Studio: Seating versus Enthusiasm through Sketching Logbook - Pranowo, Labdo; Lionar, Mario Lodeweik; Kardina, Kadek Indira Diah; Zagi, Nur Zahrotunnisaa; Kurniawan, Harry (Departement of Architecture, Universitas Islam Indonesia, 2025)
Previous studies have investigated how seating arrangement may affect students’ performance. This paper presents alternative readings on the relationships between seating in architecture studio and learning enthusiasm within the context of journaling in sketching logbook. The study was conducted upon the students in year 2023/2024 2nd-Semester Undergraduate Architecture Studio, Department of Architecture, Universitas Gadjah Mada. Logbook activities were recorded and visualized against the seating arrangements to formulate hypotheses about potential relationships. Rank-Biserial and Spearman’s ρ were used to test the strength of the correlations. The results show that (1) mobile adjacency among groups correlates positively with similarity in enthusiasm, (2) average visual proximity to all other groups correlates positively with enthusiasm, and (3) both mobile and visual proximity to the entrance correlates positively with enthusiasm. These aspects reveal possible patterns of contacts among students, leading to the conclusion that social interaction in studio is indeed significant for students’ enthusiasm. Keywords: Architecture Studio; Correlations; Seating; Quantitative Analysis